Attributions of consciousness. Issue 6 (16th September 2014) - Sytsma, Justin
Abstract : Many philosophers and brain scientists hold that explaining consciousness is one of the major outstanding problems facing modern science today. One type of consciousness in particular—phenomenal consciousness—is thought to be especially problematic. The reasons given for believing that this phenomenon exists in the first place, however, often hinge on the claim that its existence is simply obvious in ordinary perceptual experience. Such claims motivate the study of people's intuitions about consciousness. In recent years a number of researchers in experimental philosophy of mind have begun to shed light on this area, investigating how people understand and attribute those mental states that have been thought to be phenomenally conscious. In this article, we discuss the philosophical concept of phenomenal consciousness and detail the work that has been done on the question of whether lay people have this concept. WIREs Cogn Sci 2014, 5:635–648. doi: 10.1002/wcs.1320 This article is categorized under: Philosophy > Consciousness